2012
DOI: 10.5120/8142-1867
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Networks in Weather Forecasting: A Comprehensive Literature Review

Abstract: To recognize application of Artificial Neural Networks (ANNs) in weather forecasting, especially in rainfall forecasting a comprehensive literature review from 1923 to 2012 is done and presented in this paper. And it is found that architectures of ANN such as BPN, RBFN is best established to be forecast chaotic behavior and have efficient enough to forecast monsoon rainfall as well as other weather parameter prediction phenomenon over the smaller geographical region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Aviles et al, [7], have proposed Markov Chain (MC) and Bayesian Network (BN) based models for drought forecasting and used the BNs and the ranked probability skill score (RPSS) to evaluate the performance of the models in copula functions and concluded that the above model provides better forecast of droughts. Ali et al, [6], have used a multilayer perceptron neural network (MLPNN) algorithm for drought forecasting and found that the MLPNN has potential capability for SPEI drought forecasting based on performance measures, like Mean Average Error (MAE), the coefficient of correlation (R), and Root Mean Square Error (RMSE) and finally they have concluded that the above ANN model is very useful for forecasting drought.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aviles et al, [7], have proposed Markov Chain (MC) and Bayesian Network (BN) based models for drought forecasting and used the BNs and the ranked probability skill score (RPSS) to evaluate the performance of the models in copula functions and concluded that the above model provides better forecast of droughts. Ali et al, [6], have used a multilayer perceptron neural network (MLPNN) algorithm for drought forecasting and found that the MLPNN has potential capability for SPEI drought forecasting based on performance measures, like Mean Average Error (MAE), the coefficient of correlation (R), and Root Mean Square Error (RMSE) and finally they have concluded that the above ANN model is very useful for forecasting drought.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many types of neural networks used to solve classification, regression and clustering problems. NN has been utilized for diverse applications like precipitation prediction [7][8][9], water resources studies [10], meteorology and oceanography [11], weather forecasting [12,13], climate variability [7,9] and other climate-related studies. Neural networks have been found useful to extract the non-linear relationships in climate variables [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial Neural Network (ANN) algorithms have been successfully applied in rainfall classification. Among the different ANN algorithms applied, the Backpropagation Neural Network (BPN) and Radial Basis Function Network (RBFN) are the two most commonly used in rainfall prediction and yield satisfactory results [4]. However, there is no research on verifying which method applied better accuracy result as comparing to the other.…”
Section: Introductionmentioning
confidence: 99%